Impact of low-level laser therapy on the quality of life of patients with xerostomia undergoing head and neck radiotherapy: a systematic review - Ribeiro, Lucas Nascimento; de Vasconcelos Carvalho, Marianne; de Oliveira Limirio, João Pedro Justino [UNESP]; do Egito Vasconcelos, Belmiro Cavalcanti; Moraes, Sandra Lúcia Dantas; Pellizzer, Eduardo Piza [UNESP] (Springer Nature, 2024)
PurposeTo carry out a systematic review to assess whether low-level laser therapy can improve the quality of life of patients with xerostomia undergoing head and neck radiotherapy.MethodsA systematic search was performed through Embase, Medline/PubMed, Cochrane, Scopus, Web of Science, nonpeer-reviewed clinicaltrials.gov and LILACS. The strategy included clinical studies were selected that prospectively followed or evaluated the quality of life by directly comparing the use of low-level laser therapy for xerostomia induced by head and neck radiotherapy with alternative therapies without the use of a laser. The risk of bias in the studies was assessed by RoB 2.0 and Robins I.ResultsAfter all application of the predetermined criteria, four studies were included, dated between the years 2014 and 2023. Three studies described as randomized clinical trials were included, one of which was a randomized pilot study and only one was a prospective clinical trial. A total of 126 patients were evaluated, all four studies used the infrared wavelength, with two studies using the combination with the red wavelength. It was observed that low-level laser therapy can change the sensation of dry mouth, improving patients' quality of life. In addition, changes related to increased stimulated and unstimulated salivary flow were also identified.ConclusionThe use of low-level laser therapy has promising results on xerostomia, consequently improving the quality of life of patients undergoing radiotherapy in the head and neck region.